(untitled) (Journal of Technology and Operations Management, 2015)
The purpose of this paper is to examine a number of major theoretical and empirical contributions in the field if intellectual capital with an attempt to identify the major components of intellectual capital. Today the concept of intellectual capital is increasingly recognized as one of the most important strategic assets of organizations in knowledge-based economy. In knowledge-based economy, modern and high tech enterprises not only focus on innovation of new products, services, and marketing, research and development activities but also pay particular attention to the development and management of organization intellectual capital.